Inequity in Indian health care. - Purohit, Brijesh C. (Singapore Springer Nature, 2017)
This book addresses major aspects of inequity, such as access, financing, financial risk protection, gender, service delivery and utilization, in the healthcare sector in India,. Further, it discusses various measures for defining inequity in each of these aspects, and employs different indices for each dimension of inequity, which include financing, utilization, region, health outcomes, caste and class, and gender.
Keywords: Equality; Medical economics; Social justice; Health services administration